THE LEGAL PROTECTION FOR TRANSPORT PASSENGERS DURING THE COVID-19 PANDEMIC - Retno Hadiningtyas (Jurnal Pembaharuan Hukum, 2021)
Transportation as a means of supporting economic development and community development and industrial growth needs to get the main attention when conditions enter the New Normal Era because Indonesia is still experiencing a high level of spread where the mode of transportation used by many people can be a medium of spreading the COVID-19 virus. The purpose of this research is to provide legal protection to passengers by the carrier as an effort to care about the safety, comfort, safety of passengers as users of transportation services that the carrier must protect by adjusting existing regulations and in its implementation required supervision from the Government and the public. This research is normative legal research that uses a legislative approach and is sourced from primary legal materials. The data was collected by studying libraries sourced from primary, secondary, and non-legal legal materials. The research results prove that the legal protection of passengers by the carrier can run well if the passengers consciously adhere to the Health Protocol and comply with government rules as a form of effort to maintain all transportation elements with all activities. So these efforts have an impact on preventing the spread of the COVID-19 virus that is increasing in Indonesia.